The Role of Fintech and Digital Transformation in Renewable Energy Growth in Indonesia - Irna Puji Lestari; Galuh Tri Pambekti (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
Renewable energy is an alternative energy that can be used to increase economic growth and people's welfare while saving the earth. This study aims to identify the role of fintech and digital transformation as a long-term financing scenario for renewable energy growth, from both the production and consumption sector. This study uses time series data from January 2019 to September 2022 with a two-stage test. First, conducting the ARDL model estimation to find the nexus between fintech, digital transformation, and renewable energy in the short and long term. Secondly, a regression analysis was performed to capture themoderating effect of digital transformation which intermediates the influences of fintech on renewable energy. The findings conclude that fintech, digital transformation, and renewable energy have integrated relationships in the short and long term both in the production and consumption sectors. The finding also provides various recommendations for enhancing renewable energy growth, particularly through the use of accelerated fintech by digital transformation.